2021
DOI: 10.1016/j.jdsr.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Osteoimmunology drives dental implant osseointegration: A new paradigm for implant dentistry

Abstract: There is a complex interaction between titanium dental implants, bone, and the immune system. Among them, specific immune cells, macrophages play a crucial role in the osseointegration dynamics. Infiltrating macrophages and resident macrophages (osteomacs) contribute to achieving an early pro-regenerative peri-implant environment. Also, multinucleated giant cells (MNGCs) in the bone-implant interface and their polarization ability, maintain a peri-implant immunological balance to preserve osseointegration inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 125 publications
1
53
0
Order By: Relevance
“…Despite the intense usage of M1 and M2 designation (pro-vs. anti-inflammatory, respective), many have noted that such as dichotomy is overly simplistic and leads to confusion [ 488 ]. The overall potential to modulate immune signaling to create local pro-regenerative environments is immense [ 489 ] and has led to reexamination of formerly accepted dogma [ [490] , [491] , [492] , [493] ]. Indeed, recent attention has been paid to harnessing the body's natural responses to percutaneous devices via immunomodulation instead of simply delivering ineffective antimicrobials [ 494 , 495 ].…”
Section: Future Perspectives and Avenues For Innovation And Inspirati...mentioning
confidence: 99%
“…Despite the intense usage of M1 and M2 designation (pro-vs. anti-inflammatory, respective), many have noted that such as dichotomy is overly simplistic and leads to confusion [ 488 ]. The overall potential to modulate immune signaling to create local pro-regenerative environments is immense [ 489 ] and has led to reexamination of formerly accepted dogma [ [490] , [491] , [492] , [493] ]. Indeed, recent attention has been paid to harnessing the body's natural responses to percutaneous devices via immunomodulation instead of simply delivering ineffective antimicrobials [ 494 , 495 ].…”
Section: Future Perspectives and Avenues For Innovation And Inspirati...mentioning
confidence: 99%
“…Inflammation is the main mechanism of innate immunity; therefore, an initial and well-controlled inflammatory immune response is essential for bone formation and osseointegration (Trindade et al, 2018). Amengual-Peñafiel et al reported in a recent review article that immunomodulatory strategies focused on host osteoimmunology are a promising approach and that osteoimmunology will allow a better understanding and integration of the concept of osseointegration in the future (Amengual-Peñafiel et al, 2021).…”
Section: Trends; Next Generation Coatingsmentioning
confidence: 99%
“…Clot formation, platelets, and the fibrin matrix serve as the scaffold for the migration, proliferation, and differentiation of leukocytes and mesenchymal cells. This process takes place 1 to 3 days after implant placement [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%